Imagens que falam: um estudo de caso de uma menina com queixa de abuso sexual - Arruda, Camila Parducci (2017)
In the world’s population, about 20% of women and 5% to 10% of men report having been sexually abused in childhood (WHO, 2014). This research approached the theme from the theory and practice of Analytical Psychology, and aimed at conducting a clinical study of a five year old girl with a complaint of sexual abuse. The psychodynamics and emotional state of the child are described based on an interpretive and symbolic analysis of her graphic and verbal expressions. The qualitative method used was that of the case study. The analysis is based upon impressions gained and data gathered during six psychodiagnostic sessions that included anamnesis with the mother of the child, application of HTP, CAT-A, drawing of the Person in the Rain, spontaneous graphic productions, observations of play and the child’s behavior. The case study identified signs of complex trauma (VAN DER KOLK, 2005), with characteristics that frequently occur in cases of child sexual abuse, such as dissociative defenses, sadness, lowered self-esteem, insecurity, graphic expressions of imprisonment and contents that clearly held sexual connotations. It was found that the therapeutic setting offers a protective and all-encompassing place for the expression of anguish and pain in cases of victimization and/or complaint of sexual abuse, as well as for the symbolic disclosure of the trauma and its consequences. The study concludes that early psychological intervention is fundamental to minimize severe prognosis when child sexual abuse is suspected and to assist the child in his/her development